REPORT OF THE COMMITTEE ON THE STUDY OF THE FORD AND CARNEGIE FOUNDATION REPORTS. - Canning, Robert J.; Dickey, Robert I.; Herbert, Leo; Kell, Walter G.; Schiff, Michael; Smith, Frank P.; Van Voorhis, Robert H.; Schmidt, Leo A. (The Accounting Review, 1961)
This article presents the findings of the report of the committee, appointed by President Charles J. Gaa as a task committee operating under the Joint Committee on Education, to receive and review the Ford and Carnegie reports for the American Accounting Association. The two reports–"Higher Education for Business" by Gordon and Howell, and "The Education of American Businessmen" by Pierson were financed and sponsored by The Ford Foundation and the Carnegie Corporation of New York respectively. The authors of Ford and Carnegie reports, in their extensive surveys found glaring examples of bachelor's degrees given for programs of study, overloaded with business in general or with accounting in particular. The Committee urges that the faculty of each school should read the entire reports so that by carefully trying on each shoe of criticism they may find those, which fit their particular situations. It is also expected that the Ford and Carnegie reports will have an impact on collegiate education for business.